Polytherapy and Multimorbidity Pattern of Users of Anti-VEGF Drugs and Dexamethasone for the Treatment of Age-Related Macular Degeneration and other Vascular Retinopathies in Clinical Practice - Ersilia Lucenteforte; Marco Finocchietti; Antonio Addis; Mauro Tettamanti; Monica Varano; Mariacristina Parravano; Gianni Virgili (MDPI AG, 2023)
Introduction: Our aim was to describe the polytherapy and multimorbidity pattern of users of anti-VEGF and dexamethasone drugs for the treatment of these conditions, and to investigate their polytherapy and multimorbidity profiles, together with adherence and the burden of care. Methods: Descriptive, population-based, pharmacoepidemiology study on the users of anti-VEGF drugs, and secondarily intravitreal dexamethasone, for the treatment of age-related macular degeneration and other vascular retinopathies in clinical practice, using administrative databases of Lazio region, Italy. We used a cohort of 50,000 residents in Lazio in 2019 with same age as comparison. Polytherapy was assessed using databases of prescribed drugs intended for outpatient use. Multimorbidity was investigated with additional sources, such as hospital discharge records, outpatient care records, and disease-specific exemptions from co-payment. Each patient was followed for 1 to 3 years from the first intravitreal injection received. Results: 16,266 residents in Lazio who received the first IVI from 1 January 2011 to 31 December 2019, with at least 1 year of observation before index date, were included. The proportion of patients with at least one comorbidity was 54.0%. Patients used an average 8.6 (SD 5.3) concomitant drugs other than anti-VEGF used for injections. A large percentage of patients (39.0%) used 10 or more concomitant drugs, including antibacterials (62.9%), drugs for peptic ulcers (56.8%), anti-thrombotics (52.3%), NSAIDs (44.0%), and anti-dyslipidaemics (42.3%). The same proportions were found across patients of all ages, probably due to high prevalence of diabetes (34.3%), especially in younger age groups. When stratified by diabetes, a comparison of multimorbidity and polytherapy with a sample of 50,000 residents of the same age found that patients receiving IVIs used more drugs and had more comorbidities, particularly in non-diabetics. Lapses of care, whether short (absence of any type of contact for at least 60 days in the first year of follow-up and 90 in the second year) or long (90 days in the first and 180 days in the second year) were common: 66% and 51.7%, respectively. Conclusions: Patients receiving intravitreal drugs for retinal conditions have high multimorbidity and polytherapy rates. Their burden of care is aggravated by the large number of contacts with the eye care system for examinations and injections. Pursuing Minimally Disruptive Medicine to optimise patient care is a difficult goal for health systems, and more research on clinical pathways and their implementation is warranted.